PENYELIDIKAN TINDAK PIDANA TERHADAP KASUS MASSA YANG MENGHAKIMI ORANG YANG DIDUGA MELAKUKAN TINDAK PIDANA PENCURIAN YANG MENGAKIBATKAN KEMATIAN (STUDI KASUS PENCURIAN DI SWALAYAN ALFAMART JALAN KUANTAN RAYA KECAMATAN LIMAPULUH) - Jordan Nathanael Saragih; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The development of the era in the life of society in a region will always be accompanied by the increase of various criminal acts that occurred in the region, this also happens in the jurisdiction of the Police Sector Tenayan Raya where there is a mass problem that judges the person allegedly committing criminal act of theft resulting in death (case study of theft at the Alfamart Alfamart Street Kuantan Raya District Limapuluh) that occurred in 2016, but in 2017 a mass case that judges a person suspected of committing the crime of burglary that resulted in the death has not been resolved completely and is still under investigation by the police.In the investigation conducted by the Police Sector Tenayan Raya on mass cases that judge people suspected of committing the act of theft resulting in death (case study theft in Alfama Street Alfamart Jalan Kuantan Raya District Limapuluh) experienced bebagai kind of kedala or inhibiting factors in the investigation of one of the lack The source of information in the community around the place of the occurrence of vigilante action does not know the occurrence of such vigilante acts. Therefore, the investigation of criminal acts against mass cases that judge people suspected of committing criminal acts of theft resulting in death (the case of theft in Alfamart Street Kuantan Raya District Limapuluh) has not been resolved thoroughly.From the results of research problems encountered by the Police Sector Tenayan Raya can be concluded, namely: First, the investigation conducted by the Police Sector Tenayan Raya on mass cases that judge people suspected of committing criminal theft (case study theft in supermarkets Alfamart Street Kuantan Raya District Limapuluh). Second, the obstacle or the inhibiting factor experienced by the Police Sector Tenayan Raya in conducting the investigation is the lack of information considering the location of the theft occurred in the territory of the Police Sector Limapuluh. Third, efforts made by the Police Sector Tenayan Raya in overcoming obstacles one of them is to cooperate with the Police Sector Limapuluh to overcome obstacles in the lack of information.Keywords: Investigation-Criminal-Action-Eigenrichting